The Effect of Internal Control and Compensation on Honorary Employee Performance (Case Study of BAPENDA Southeast Sulawesi Province) - Andi Basru Wawo; Andi Muh. Fuad; Si Made Ngurah Purnaman; R Rahmiati (CV. Media Digital Publikasi Indonesia, 2024)
This study aims to test and explain the Effect of Internal Control and Compensation for the Performance of Temporary employees. The independent variable in this study is Internal Control and Compensation, while the dependent variable in this study is the Performance of Temporary employees. Data collection method used aquestionnaire. The data analysis used the descriptive analysis method and multiple linear regressionanalysis. This research also uses factor analysis to show the most influential indicators in one variable. The result of this study indicate that (1) the internal control variabel has t-count > t-tabel and significance value < significance level (2) compensation variable has t-count > t-table and significant value< signivicance level (3) internal control variable and compensation for the performance of Temporary employees has a value of t-count > f-table and a significant value of significance level.